Ascorbic acid as an elicitor of salt stress on the physiology and growth of guava - Torres, Rafaela Aparecida Frazão (2024)
The objective of this study was to evaluate the physiology and growth of guava cv. Paluma as a function of irrigation with saline water and foliar application of ascorbic acid. The study was conducted using a randomized block experimental design in a 5 × 4 factorial scheme, whose treatments were formed by combining five levels of electrical conductivity of irrigation water - ECw (0.3, 1.2, 1.9, 2.6, and 3.3 dS m-1), associated with four concentrations of ascorbic acid - AsA (0, 30, 60, and 90 mM), with three replicates and one plant per plot. Stem diameter, crown volume, vegetative vigor index, photosynthetic pigment contents, photochemical efficiency, electrolyte leakage, and relative water content were evaluated. Ascorbic acid at concentration of 60 mM increased electrolyte leakage and relative water content in plants under ECw of 3.2 and 2.9 dS m-1, respectively. AsA concentration of 90 mM stimulated the biosynthesis of chlorophyll a, chlorophyll b, and total chlorophyll of guava plants grown under water salinity of 3.3 dS m-1. Salinity above 0.3 dS m-1 reduced chlorophyll a fluorescence, crown volume, and vegetative vigor index of guava. Foliar application of 30 mM ascorbic acid increased the quantum efficiency of photosystem II up to ECw of 2.5 dS m-1. The beneficial effect of ascorbic acid was obtained under ECw of 0.3 dS m-1.